Lean production and TQM: Complementary or contradictory driving forces of innovation performance? - Aoun, Malak; Hasnan, Norlena (Multi-Science Publishing, 2013)
As a set of tools and standards, Total Quality Management (TQM) tends to focus on individual processes to improve the productivity and efficiency of organizations. For the same objective, many organizations adapt the Lean production system in their strategies to eliminate waste and reduce the non-value-adding activities. Thus, organizations are looking for innovative ways to achieve more with fewer resources. Yet, innovations are restricted because the process of generating new ideas and making effective decisions is limited to just a few people, and no broad employee participation is achieved, resulting in the waste of intellectual talent. This paper aims to discuss the impact of both Lean production and TQM on innovation performance. In addition, it presents a conceptual model to understand this relationship, supported by literature review from recent studies. This discussion provides insights into more specific features related to Human Relations Management and Improvement Strategies that can be utilized to advance the intellectual capabilities at any organization, thereby providing chances of successful innovation performance.